Strength diagnostics in skiing: a summary of jumping profiles of elite athletes in skiing sports - Snyder, C.; Stöggl, T. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: A wide variety of lower extremity strength diagnostics are regularly used to assess strength and power profiles in various winter sports 1. Although the sport-specific demands of each discipline are unique, common diagnostic methods, such as unloaded and loaded jumping are used across all disciplines. The purpose of this study was to identify interchangeability between testing modalities 2, as well as differences between disciplines to identify the most relevant strength diagnostics for various winter-sport disciplines.